Beberapa Pengamatan Ibn Hazm (M.456H/1063M) Terhadap Mantik Greek dari Sudut Akidah Islam: Tumpuan Kepada Perbahasan Al-Tasawwurat - Hamat, Mohd Fauzi (Jurnal Usuluddin, 1998)
This article tries to elaborate some aspects of lbn Hazm’s observation upon logic as a discipline introduced by Greek thinkers. Special emphasize is given to his commentary to the concept of al-tasawurat which include the discussion of certain topics like al- kulliyat al-khams (the predicable), al-ta’rif (definition) and al- maqulat (categories). His interpretation about the relation between aqeeda and Greek thinking in relation to those topics will be discussed in this article.